Environmental Sustainability Game For Elementary School Students (Green Genie) - Goh, Mei Kei (2023)
Environmental sustainability is to stabilize the existing strained relationship between human civilization and the living world. However, humans are depleting and destroying the earth’s resources faster than they can be restored and regenerated. The major reason for this is because most individuals have a poor level of environmental awareness regarding recycling. It is critical to start teaching children about the need of recycling and living an eco-friendly lifestyle as early as possible so that they learn that not everything or all resources are infinite. Therefore, this project is to turn the idea into an educational entertainment game for children aged 7 and up in order to spark their interest in recycling and environmental concerns in this game project. The objectives of this game project is to study the existing environmental sustainability game for elementary school students, develop an environmental sustainability game that provides recycling knowledge for elementary school students and evaluate the functionality of the developed environmental sustainability game for elementary school students. The game is a personal computer (PC) based game and it develops by using Unity game engine. First-Person Shooter (FPS) game genre will be implemented in this game project to enhance the children’s interest in playing the recycle game. All the items that collected by the players will convert into ammo for the Blasters and shoot to the corresponding recycle bin. The result through this project is that player can learn about the categorizing of garbage and practice to do the recycle. There are also hidden messages delivered to the players alerting them that improper waste management might lead to the spread of germs and harm living things, particularly aquatic life.